Challenges and Strategies of Moral Faith Teachers in Instilling Character in the Era Digital at Mtsn Parepare - Hermin; Herdah; Nurhayati (IAIN Parepare, 2025)
This thesis aims to describe the challenges and strategies applied by moral faith teachers in instilling character in the digital era in students at MTsN Parepare. This study uses a type of qualitative approach with an ex post facto type of research that is descriptive in the form of field research and direct data collection through observation and interviews with PAI MTsN Parepare teachers. The research paradigm used is a qualitative descriptive paradigm that seeks to understand in depth the social and educational reality that is taking place in schools. The results of this study explain that teachers of Moral Faith at MTsN Parepare face various challenges in cultivating students' character in the digital era, such as the negative influence of social media, lack of awareness of digital ethics in students, and limited time in a dense curriculum. The challenge of teachers in implementing strategies is the use of digital media as a means of learning, problem-based learning methods, as well as discussions and simulations related to moral issues in cyberspace, while guiding students through self-reflection and example. The strategy has shown positive results although not fully optimal, but with consistent and continuous implementation students are beginning to be able to understand and practice character values in their digital lives.